1994
DOI: 10.1177/002193479402500102
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Voices of Black Men

Abstract: Specifically, men's roles as economic providers or as patriarchs have been central to this work. Black males' struggles with manhood, whether a byproduct of structural barriers, cultural pathology, or both, are implicated as a contributor to the rates of female-headed households, never-married childbearing, and divorce in Black communities (Liebow, 1967;Staples, 1982;Wilson, 1987). However, the meaning of manhood has been treated as largely unidimensional and universal-man as economic provider and as head of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(61 citation statements)
references
References 18 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…Hammond and Mattis (2005) described it as being developed within an interdependent process in connection to others. This paralleled Hunter and Davis’ (1992, 1994) findings, Mattis, Hearn, and Jagers’ (2002) research on communalism, and Wade’s (1998) relational theory of African American masculinity. These relational constructions may extend to men’s need to belong to in-groups.…”
Section: Theoretical Framework: African American Masculinity and Desimentioning
confidence: 52%
“…Hammond and Mattis (2005) described it as being developed within an interdependent process in connection to others. This paralleled Hunter and Davis’ (1992, 1994) findings, Mattis, Hearn, and Jagers’ (2002) research on communalism, and Wade’s (1998) relational theory of African American masculinity. These relational constructions may extend to men’s need to belong to in-groups.…”
Section: Theoretical Framework: African American Masculinity and Desimentioning
confidence: 52%
“…34,[51][52][53][54] While it is a key contributor to the poor social and economic outcomes of minority men, 40,[55][56][57][58][59] theories explaining how manhood is a determinant of minority men's health are underdeveloped. Definitions and practices of manhood vary by time, location and person, but notions of manhood and social determinants of men's health have not adequately considered men's social status, economic position, or relations among men as determinants of health.…”
Section: An Intersectional Approach To Manhood and Minority Men's Healthmentioning
confidence: 99%
“…Many African American researchers have been dissatisfied with the concepts and explanations social scientists have used to explain the psychological functioning of African American men (Conner & White, 2006;Hunter & Davis, 1994;Johnson, 2006;Mattis et al, 2004;Morton & Toldson, 2012). The counseling literature has almost completely neglected effective and constructive features of the psychological functioning of African American men (Jenkins, 1995).…”
mentioning
confidence: 99%
“…The counseling literature has almost completely neglected effective and constructive features of the psychological functioning of African American men (Jenkins, 1995). Hunter and Davis (1994) identified that much of the literature on African American men has focused on the stripping away of manhood, ignoring the fact that, even under the worst circumstances, African American men have managed to develop a sense of dignity and self-worth. A dramatic example of this can be found in the 1968 Memphis sanitation workers' strike (Estes, 2005).…”
mentioning
confidence: 99%